A Reflection on Longitudinal Family Medicine - Smith, Alyssa; Shum, Lucy; Johnson, Burnett (McGill Journal of Medicine, 2017)
During their first year of medical school McGill students take part in the Longitudinal Family Medicine Experience program. This unique program pairs each student with a practicing family medicine physician across the island of Montreal and allows students to shadow and experience firsthand a primary care practice. Throughout approximately a dozen half-day sessions during their first year, students are exposed to the entire spectrum of family medicine practices; in the emergency department, Centres locaux de services communautaires (CLSCs), labour and delivery rooms, home visits and refugee clinics. This unique, integrated program was designed in tandem with McGill medical school’s new curriculum to allow early exposure to the depth and breadth of community practice and family medicine. Each year as they complete their LFME sessions students complete a reflective essay looking back on their experiences and highlighting personal learning points. Below are three examples of these essays which have been chosen to highlight the diverse nature of family medicine.